Analiza wybranych aspektów rynku owocników pieprznika jadalnego (Cantharellus cibarius Fr.) - Piętka, Jacek; Kowalczuk, Dawid; Staniszewski, Paweł (Leśne Prace Badawcze, 2012)
This paper presents an analysis of data on the purchase of Cantharellus cibarius Fr. fruit bodies in the vicinity of Czeremcha village. The volume purchased from seven local purchasing centres between 2004-2008 was compared to temperature and precipitation data. In each of these years, the relationship between the volume purchased and the total precipitation each month was noted. The average price of the fruit bodies of C. cibarius was 10.05 PLN/kg, which was much higher than that of other fungal species: Xerocomus badius (2.44 PLN), Suillus luteus (2.47 PLN), and even Boletus edulis (6.50 PLN). In the years 2004–2008, the mass of purchased fruit bodies of C. cibarius purchased accounted for 63% of all fungi, which indicates that C. cibarius is the most important species among the forest edible mushrooms in the Polish market. The existing regulations applicable to the forest mushroom utilization and trade are also discussed.